2016
DOI: 10.1504/ijbaaf.2016.079165
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the overall performance of microfinance institutions

Abstract: In recent years, there has been a growing interest in microfinance institutions (MFIs). Some studies assess the financial condition of MFIs on the basis of individual criteria while a few others attempt to explain differences in profitability on the basis of firm-level attributes and country-level characteristics. However, there is no widely accepted measure for assessing the performance of MFIs. At the same time, these institutions face a challenge, as they have to provide financial services to the poor, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This finding indicates that MFIs earn a higher profit while having a higher DTE ratio of MFIs. Gaganis (2016) investigated the relationship between GDP and performance of MFIs, with results showing a positive relationship between GDP and MFIs' overall performance. This finding might be seen as implying that good economic performance can boost the productivity of MFIs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that MFIs earn a higher profit while having a higher DTE ratio of MFIs. Gaganis (2016) investigated the relationship between GDP and performance of MFIs, with results showing a positive relationship between GDP and MFIs' overall performance. This finding might be seen as implying that good economic performance can boost the productivity of MFIs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the other hand, Donou-Adonsou & Sylwester (2017) found a negative correlation between real GDP and microfinance growth, a result that seems to indicate that the higher the real GDP functions in a country, the lower the microfinance growth in the country is. Gaganis (2016) examined the relationship between inflation and the efficiency of MFIs and found no significant relationship, i.e. a higher or a lower inflation rate does not affect the efficiency of MFIs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This indicated that the higher DTE ratio of MFIs, the higher the profits they earn. Gaganis (2016) investigated the relationship between GDP and the performance of MFIs. Results showed there is a positive relationship between GDP and MFIs’ overall performance.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…This implied that higher inflation will lead to poorer profitability of MFIs and they will obtain a benefit if the formal financial system is stable. Gaganis (2016) investigated the relationship between inflation and efficiency of MFIs and found no relationship results. This implied that a higher or lower inflation rate does not affect the efficiency of MFIs.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation